2010
DOI: 10.1007/s11738-010-0634-3
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian sex hormones stimulate antioxidant system and enhance growth of chickpea plants

Abstract: In the present study, it was aimed to investigate the influence of exogenous mammalian sex hormones (MSH) (progesterone, b-estradiol and androsterone) on the morphological (root and shoot growth) and biochemical parameters (protein and sugar content, antioxidant enzyme activities, and lipid peroxidation and H 2 O 2 levels) of chickpea (Cicer arietinum L.) plants growing under control conditions. The solutions of hormones prepared at different concentrations (10 -4 , 10 -6 , 10 -9 , 10 -12 and 10 -15 M) were sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 22 publications
(19 reference statements)
7
48
0
3
Order By: Relevance
“…The root growth results of this study are consistent with similar results obtained with chickpea seedlings in that exogenous application of 10 −4 -10 −12 M ES as a foliar spray resulted in enhanced root and shoot length growth [32]. Application of selected estrogens on Arabidopsis plants grown on artificial medium [15], winter wheat [33], sage (Salvia splendens) [34] and chicory (Cichorium intybus) [14] was found to stimulate flowering.…”
Section: Growth and Developmentsupporting
confidence: 89%
“…The root growth results of this study are consistent with similar results obtained with chickpea seedlings in that exogenous application of 10 −4 -10 −12 M ES as a foliar spray resulted in enhanced root and shoot length growth [32]. Application of selected estrogens on Arabidopsis plants grown on artificial medium [15], winter wheat [33], sage (Salvia splendens) [34] and chicory (Cichorium intybus) [14] was found to stimulate flowering.…”
Section: Growth and Developmentsupporting
confidence: 89%
“…Progesterone, estrone and androsterone induce in vitro flowering in Arabidopsis thaliana [25]. Exogenous application of MSHs activate the oxidative enzymes under non-stress conditions [26]. The latest results obtained in spring wheat after drought treatment [24] suggest that progesterone and its putative receptors contribute in processes regulating plant interactions with the environment.…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…The same researches reported that MSH treatment significantly increased the Na content in chickpea seeds and barley leaves. Other researches shown that although MSH treatment increased the Na, K and Ca contents in chickpea seedlings, they decreased the Cl content (Afzal et al 2006;Erdal and Dumlupinar 2011b). Erdal (2012) reported that MSH application together with salt stress increased the dry weight, sugar, proline, protein, chlorophyll, glutathione (GSH) contents, superoxide dismutase (SOD), peroxidase (POX), catalase (CAT), ascorbate peroxidase (APX), nitrate reductase (NR) activities, and reduced the lipid peroxidation (MDA) level, superoxide (O2 − ) production and hydrogen peroxide (H2O2) content compared with salinity alone.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, several studies have shown that exogenous mammalian sex hormones such as progesterone, β-estradiol and andosterone affect hydrogen peroxide (H2O2) content and lipid peroxidation monodihydroascorbate (MDA) levels by stimulating the activity of antioxidant enzymes. So these hormones have positive effects on plant growth and development under stress (Dogra and Thukral 1996;Erdal and Dumlupinar 2011b). The obtained results were thought that the protective role of β-estradiol may be from the reduced ROS levels and the effect of ROS causing epigenetic changes.…”
Section: Discussionmentioning
confidence: 98%